THE MANAGEMENT OF A CHILD-FRIENDLY CULTURE IN MINIMIZING DISCRIMINATION OF DISABILITIES CHILDREN AT HARSYA CERIA EARLY CHILDHOOD EDUCATION BANDA ACEH - Nadirah, Nani; Rahmi, Sri (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Every individual has the equal right to receive quality education, as well as the right to grow, develop, and continue their life, including the right to protection from violence and discrimination. This study aims to examine the planning and implementation of a child-friendly culture to minimize discrimination against children with special needs (ABK) at PAUD Harsya Ceria Banda Aceh. A qualitative approach was used to analyze the management of child-friendly culture in reducing discrimination against ABK at PAUD Harsya Ceria Banda Aceh. Data analysis was carried out using the Miles and Huberman model, which involves data collection, data reduction, data presentation, and drawing conclusions. The findings indicate that planning was carried out by establishing a vision, mission, and goals, along with an analysis of ABK needs, resource allocation, and engagement with all stakeholders. The implementation of a child-friendly culture involved integrating children with special needs with their peers without any boundaries or distinctions in all activities. Teachers also fostered empathy in regular children towards children with special needs, encouraging them to respect differences. The teaching process was carried out using the “KAYANG” strategy.